Cash Holding, R&D, and Financial Performance of Listed Companies in Indonesia - Cahyani Tunggal Sari (Sean Institute, 2024)
It is anticipated that this study will help businesses during the pandemic by offering guidance on tactics that will facilitate access to funding and resources for research and development. The degree of success can rise to the advantage of staff members and business owners if managers of companies can more accurately identify plans in the areas of financial resources and research and development. The three variables in this study are cash holdings, This is the dependent variable, profits per share (EPS), the mediating variable, and the independent variable is research and development. The research sample consists of businesses that are listed on the Indonesia Stock Exchange and are involved in R&D between 2020 and 2022. The data analysis procedure employed Stata software to ascertain the role that R&D activities had as a mediating variable in the relationship between cash holdings and EPS. The results of the study show that cash holdings significantly affect R&D activity but have no discernible effect on EPS. Research and development endeavors have proven to have a significant mediating effect, with a probability of less than 0.05. Consequently, during the Covid pandemic, R&D efforts in businesses contributed to better cash holding performance on EPS.